Peran Konseling Individu Mengenai Control Orang Tua Terhadap Anak-Anak Yang Menggunakan Gadget - Dian Novelia Azris; Dina Hadana; Dandi Fadhillah Ritonga; Dika Sahputra (Peneliti.net, 2023)
The development of science and techhnologhy the morre development the use of smart phones, the widespread ue of gadgets is not only happening among adults , but even children do not escape this the use gadgets in chilldren has negatif and positive impact ,thus requiring extra supervision from parents through individual counseling the purpous of study was to determine the aplication of individual counseling regarding parental control over the use of gatdgets in chilldren this study uses a quantitative approach with research methods that include a quistionaire the data analisy technique used is data presentation and conclusion drawing and data analiysis. Researchers have conducted research in SD AMALIA MEDAN and LOCAL COMMUNITIES. (10 people).